LARANGAN PETHUK BESAN DALAM TRADISI PERNIKAHAN ADAT DI WILAYAH DESA BANARAN, KECAMATAN KANDANAN, KABUPATEN KEDIRI - Aulia Nur Sahlina; Novi Siti Kussuji Indrastuti (LP2M UIN Abdul Muthalib Sangadji Ambon, 2026)
The pethuk besan prohibition is part of the traditional marriage customs in Banaran Village, Kandangan District, Kediri Regency, which forbids the parents of the bride and groom from meeting for the first 40 days after their children’s marriage ceremony. The majority of the village community still obeys this long-standing prohibition today. This research aims to describe the function of the pethuk besan prohibition from the perspective of the community that still adheres to it, using William Bascom’s theory of folklore function. The research was conducted using a descriptive qualitative method through interviews with community leaders in Banaran Village. The results indicate that the pethuk besan prohibition has several functions: (1) projection system: a symbolic representation of ideal post-marital family relations; (2) cultural validation: the myth of misfortune as a legitimization of the prohibition; (3) educational function: internalization of values and socialization of rules; and (4) social control function: regulating behavior and enforcing compliance.